Ligustrazine-induced microRNA-16-5p inhibition alleviates preeclampsia through IGF-2. Issue 6 (December 2020) - Yuan, Yuan; Zhao, Ling; Wang, Xiaoying; Lian, Feng; Cai, Yan
Abstract : Preeclampsia (PE), a serious complication of pregnancy, is associated with abnormal trophoblast cell differentiation and autophagy. Herein, we investigated the molecular mechanism underlying the function of ligustrazine (2, 3, 5, 6-tetramethylpyrazine, TMP), a constituent of the traditional Chinese plant medicine Ligusticum wallichii, in PE. Lipopolysaccharide (LPS) was applied to induce a PE rat model, followed by tail vein injection of TMP or lentiviral vector overexpressing microRNA-16-5p (miR-16-5p). Human trophoblast cell line JEG3 was cultured in vitro to construct a PE cell model, followed by t he treatment with different concentrations of TMP, miR-16-5p mimic/inhibitor, or shRNA (shRNA) against insulin growth factor-2 (IGF-2) (sh-IGF-2). Formation of autophagosomes and autophagy-related proteins were then examined. Cell counting kit-8 (CCK-8) and Transwell assays were applied to measure trophoblast cell viability and migration. The binding affinity between miR-16-5p and IGF-2 was verified by dual luciferase report assay. After TMP treatment, autophagosome formation was reduced in trophoblast cells of placental tissue of PE rats, along with downregulation of autophagy-related proteins Light Chain 3 (LC3)-II/LC3-I, Beclin1 (BECN1), and SQSTM1. Moreover, TMP repressed JEG3 cell autophagy, promoted viability and migration concentration-responsively. MiR-16-5p was upregulated in PE, and TMP inhibited miR-16-5p expression. Besides, miR-16-5p downregulated IGF-2 expression to promote cell autophagy and inhibit the viability and migration of JEG3 cells. Further, in vivo experiments validated that TMP impeded PE progression in rats by regulating the miR-16-5p/IGF-2 axis. In summary, TMP inhibits trophoblast cell autophagy and promotes its viability and migration in PE rat model through regulating the miR-16-5p/IGF-2 axis.